Peningkatan Pengtahuan Murid SMA Terkait Kesehatan Reproduksi Untuk Mencegah Stunting Di Desa Mayangrejo, Kalitidu - astri dewi choirina (Universitas Airlangga, 2021)
The period of the first 1000 days is often called the window of opportunities or often called the golden period which is a determinant of the quality of health in the next lifetime. Unfortunately, in every 1000 HPK there are various health problems that affect the health of the baby, which one of the problem is stunting. Stunting is a malnutrition condition related to insufficient nutrition. One of the factors in the occurrence of stunting is due to risky pregnancies such as pregnancy at a young age, a lack of knowledge of mothers about health and nutrition before and during pregnancy, and after giving birth. Community service efforts were carried out in Mayangrejo, Kalitidu, Bojonegoro to reduce the incidence of stunting. Community service is carried out in the form of implementing educational activities and socializing adolescent reproductive health to 11 and 12 grade students of Al-Aly Islamic High School, Mayangrejo, Kalitidu so that they can be responsible for their reproductive health and their future. This community service activity is expected to increase the knowledge and understanding of adolescents related to reproductive health and the impact of marriage and pregnancy at too young age so that it can reduce the prevalence rate of stunting toddlers in Mayangrejo.